Lietuvos vėlyvojo paleolito kultūrų periodizacija - Šatavičius, Egidijus (Archaeologia Lituana, 2005)
Lithuania’s archaeological sites of the Late Palaeolithic and earliest Mesolithic have no absolute chronological data and are dated only on the basis of environmental periodization. Thus, archaeological sites from this periods are chronologically associated with climatic chronozones - the Dryas I, Bölling, Dryas II, Allerod, Dryas III and Preboreal periods. A more specific periodization of Lithuania’s archaeological cultures of this time can presently be made only on a conjectural level. Based on the sites’ artifactual flint complexes and many neighbouring countries’ analogues, especially those that have been accurately dated, the Late Palaeolithic in Lithuanian territory can be divided into five main cultural groups (Hamburgian, Federmesser, Brommean, Ahrensburgian, Swiderian) that partially also reflect chronological periods. Two of these cultures, Hamburgian and Federmesser, arc distinguished in Lithuanian territory for the first time. Moreover, the Brommean, Ahrensburgian, and Swiderian cultures arc defined much more precisely. At present, we can only assign five small sites or artifact collections found in South Lithuania to Hamburgian culture. These are the Kašėtos collection and the sites of Varėnė-2, Ežerynas (8th locus), Margiai “Sala”, and Maksimonys-1. The flint artifacts comprising these sites arc thickly patinated and sometimes glossy from wind erosion. They are characterized by blades that have been detached by hard or soft percussion from a core having two opposite platforms, a microburin technique, shouldered and tanged Hevelte-type points, as well as large Zinken-type tools. As in North Europe, two cultural periods are distinguished in the Lithuanian artifactual complexes; the earlier period consists of shouldered points as well as large Zinken-type tools and long end-scrapers, while the later period consists of tanged Havelte-type points with smaller Zinken-type tools and scrapers (usually with retouched edges). Based on complexes in North Germany, Denmark, the Netherlands, and Poland that have been dated by 14C and TL, Hamburgian culture existed during the Balling and the beginning of the Alleröd periods (mid-11th mil. BC - mid-10th mil. BC). The small hunter communities of this culture arrived into Lithuanian territory from the territories of North Germany and West Poland. Finds characteristic of Federmesser culture have been found in excavations of the Ežerynas 8-13 loci in South Lithuania. The Federmesser culture complexes are characterized by tools made from flakes, a hard or semi-hard percussion, faceted core utilization, a microburin technique. and Federmesser points contained backed blades with a more or less curved edge, Wehlen-type flaked and small scrapers. These complexes in North Germany and Poland arc usually dated to the Alleröd period. Many more sites have been found that belong to Brommean culture. They have been discovered in all of South Lithuania and even in West Lithuania. More than 30 sites of this culture are presently known in Lithuania (Titnas-1C, Maskauka-6, Mitriškės-5n, 6a-b, Vilnius-2, Ežerynai (9, 11, 15-17th loci) Mergežeris-8, Žuvintai-1). Bromme culture is distinguished by a very archaic and rough manufacturing technology. Very heavy and irregular blanks are usually knapped from one-platformed cores by hard percussion; a sparse tool-weapon complex is made from these blanks massive and smaller tanged points, scrapers, and burins. Bromme culture sites in the entire southern and southeastern Baltic arc dated to the Alleröd’s second half and the Dryas III period’s very beginning. Bromme culture representatives came to Lithuania from the West - from the territories of Denmark and North Germany. With the cooling of the climate in the beginning of the Dryas III period, the Bromme cultural complex slowly transformed into the Ahrensburgian and Swiderian cultural complexes. Tool kits very similar to those of Bromme culture are characteristic of Ahrensburgian and Swiderian cultures: utilization of two-platformed cores and a semi-soft or soft percussion-pressure technique. About 40 Ahrensburg culture sites and isolated finds have been encountered in all Lithuanian territory (Šilelis-2, Vilnius-1, Pasieniai-1A, Rekučiai-1A, Nendriniai), except for the western region which has barely been researched. Tanged arrow points, usually without a not retouch on the dorsal side of the tang, Zonhoven microliths, a microburin technique, as well as shorter and usually side, round, or semi-round scrapers are characteristic of this culture. Also, bur ins, various special purpose tools, perforators, naked axes, and other tools are found at these sites. Ahrensburg culture existed during the entire Dryas III period, while during the beginning and middle of the Preboreal it developed into the Pypliai-1C-type complex. Ahrensburgian sites are found in large expanses throughout North Europe and even in the northern part of the Scandinavian peninsula, beyond the Arctic circle. So far, about 130 sites and isolated finds belonging to the Swiderian culture have been distinguished. They are found throughout the whole Lithuanian territory, especially south of the Nemunas and Neris rivers. Characteristic of these Swiderian complexes are points that are both tanged or without tangs and have a flat retouch on the dorsal side, long end-scrapers on blades, single, dihedral and retouched burins, perforators, special purpose tools, axes. According to the dated complexes of Witów, Całowanie (both in Poland), and Kabeliai-2C, Swiderian culture is divided into two periods, the older of which is dated to 8800-8500 BC (it is characterized by points with clearly distinguished tangs and usually an obliquely retouched top), and the younger to 8400-7800 BC (it is characterized by points without tangs). In the beginning of the Preboreal, Swiderian’ culture slowly transformed into Kunda culture, the Pasieniai-1 type sites being a transitional form between these two cultural groups. Swiderian culture sites are found in the territories of Lithuania, Poland, North Ukraine, Belarus, Northwest Russia, and Latvia. Isolated complexes are found even in Czechia, East Germany and Crimea.